PENDAMPINGAN IMPLEMENTASI DEEP LEARNING DALAM MANAJEMEN KURIKULUM BAGI KEPALA SEKOLAH TK DAN PAUD DI SURAKARTA - Muhammad Jafar Nashir; Iffah Mukhlisah; Lailla Hidayatul Amin; Rasyid Fadhli (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2026)
Early childhood education requires innovative and adaptive curriculum management to support meaningful learning in line with the Merdeka Curriculum. However, several kindergarten and early childhood education principals in Surakarta still experience limitations in understanding and implementing the deep learning approach in curriculum management. These problems are reflected in the low ability of principals to design project-based learning, conduct academic supervision, and develop child-centered authentic assessment. This community service activity aimed to improve principals’ competencies in implementing deep learning in early childhood curriculum management. The service method used a Participatory Action Research (PAR) approach involving 25 kindergarten and early childhood education principals through stages of problem identification, needs assessment, program planning, training, workshops, implementation assistance, monitoring, and evaluation. The results showed an increase in participants’ understanding of deep learning implementation in curriculum management, with the average score increasing from 58 to 84. In addition, there were changes in learning practices that became more child-centered through the implementation of project-based learning, exploratory activities, and authentic assessment. This community service activity also contributed to the establishment of a principals’ learning community and the emergence of local leaders who support the sustainability of learning innovation in early childhood education environments. Therefore, assistance in implementing deep learning was proven to improve principals’ capacities while encouraging the transformation of early childhood learning culture to become more collaborative, reflective, and meaningful.